2020
DOI: 10.1016/j.scib.2020.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Absence of murine CFAP61 causes male infertility due to multiple morphological abnormalities of the flagella

Abstract: Abnormal expression of cen-trosome protein (centrin) in spermatozoa of male human infertility Chinese Science Bulletin 47, 822 (2002); A TOP6BL mutation abolishes meiotic DNA double-strand break formation and causes human infertility Science Bulletin 65, 2120 (2020); Male infertility caused by microbial infection and immunological disorder SCIENTIA SINICA Vitae 47, 180 (2017); Effects of soil amplification ratio and multiple wave interference for ground motion due to earthquake

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
5
15
0
Order By: Relevance
“…Almostall Cfap61 −/− spermatozoa were abnormal and showed short, bent, curled, thick or missing flagella (Figure 5-figure supplement 1). Similar phenotypes were reported in a contemporaneous study of another Cfap61 knockout mouse(Huang et al, 2020). The acrosome morphology of Cfap61 −/− sperm was normal, while the formation of the tail was clearly disordered (Figure 5B-F).…”
Section: Resultssupporting
confidence: 82%
“…Almostall Cfap61 −/− spermatozoa were abnormal and showed short, bent, curled, thick or missing flagella (Figure 5-figure supplement 1). Similar phenotypes were reported in a contemporaneous study of another Cfap61 knockout mouse(Huang et al, 2020). The acrosome morphology of Cfap61 −/− sperm was normal, while the formation of the tail was clearly disordered (Figure 5B-F).…”
Section: Resultssupporting
confidence: 82%
“…Since disruption of Cfap61 in mice was associated with the abnormalities of flagellum components (Huang et al, 2020), we thus investigated the ultrastructure of spermatozoa from the patients (P1-P6, P8, and P9) by TEM. In contrast to the typical "9 + 2" axoneme arrangement in the spermatozoa from a fertile control, most of the flagellar cross-sections from spermatozoa of patients exhibited severely disorganized axoneme structure, along with the missings of MTDs, dynein arms, RSs, and/or CP (Figure 2A).…”
Section: Homozygous Variants In Cfap61 Were Found In Patientsmentioning
confidence: 99%
“…Biallelic mutations in CFAP91 and CFAP251 have been reported in MMAF-affected individuals (Auguste et al, 2018;Kherraf et al, 2018;Li et al, 2019;Martinez et al, 2020). Moreover, Cfap61 knockout mice displayed multiple morphological and ultrastructural abnormalities, severely reduced sperm count and motility, and male infertility (Huang et al, 2020). Nonetheless, whether CFAP61 variants are also associated with MMAF in humans and the clinical manifestations of the CFAP61 genetic anomalies have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The cilia and flagella associated protein (CFAP) family, such as CFAP58, CFAP61, CFAP69, CFAP65, CFAP43, CFAP44, CFAP70, and CFAP251, is associated with flagellum biogenesis and morphogenesis (Tang et al, 2017;Dong et al, 2018;Beurois et al, 2019;He et al, 2020;Huang et al, 2020;Li et al, 2020). Previous studies have indicated that the functional role of CFAP53 (also named the coiledcoil domain containing protein CCDC11) is involved in the biogenesis and motility of motile cilia (Perles et al, 2012;Narasimhan et al, 2015;Noël et al, 2016;Silva et al, 2016), and CFAP53 is localized not only to the base of the nodal cilia, but also along the axoneme of the tracheal cilia (Ide et al, 2020).…”
Section: Introductionmentioning
confidence: 99%